The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1471-2431-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene instruction decreases illness-related absenteeism in elementary schools: a prospective cohort study

Abstract: BackgroundIllness-related absences have been shown to lead to negative educational and economic outcomes. Both hand washing and hand sanitizer interventions have been shown to be effective in reducing illness-related absences. However, while the importance of hand hygiene in schools is clear, the role of instruction in use is less obvious. The purpose of this study was to compare absenteeism rates among elementary students given access to hand hygiene facilities versus students given both access and short repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 17 publications
4
47
0
2
Order By: Relevance
“…18 Illness related absenteeism have been found to be reduced by hand washing interventions. 19 In a school based study conducted by Lopez-Quintero, 2009, it was found that few children reported gastrointestinal symptoms in the preceding month and absenteeism in last year. 20 An intervention based study needs to be carried out to study the implication of proper hand washing behaviour on illness and related absenteeism in the present study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Illness related absenteeism have been found to be reduced by hand washing interventions. 19 In a school based study conducted by Lopez-Quintero, 2009, it was found that few children reported gastrointestinal symptoms in the preceding month and absenteeism in last year. 20 An intervention based study needs to be carried out to study the implication of proper hand washing behaviour on illness and related absenteeism in the present study population.…”
Section: Discussionmentioning
confidence: 99%
“…19 In an interventional study conducted in Kolkata in primary school children it was found that 85.4% children washed their hands before eating food while 55.2% washed hands after going to the toilet. 27 Hand washing after going to the toilet was practiced by 55.2% of the respondents in a study conducted in south India.…”
Section: Discussionmentioning
confidence: 99%
“…5,[11][12][13] Hand sanitizer interventions conducted in elementary schools in the United States have reduced illness-related absenteeism by 14-51%. 3,[14][15][16][17] Home-based hand sanitizer interventions have also been found to reduce respiratory and gastrointestinal illness transmission among households with children enrolled in daycare. 18,19 Alcohol-based hand sanitizers have limited efficacy against some enteric pathogens, such as the sporeforming bacteria Clostridium difficile and Norwalk virus.…”
Section: Introductionmentioning
confidence: 99%
“…Washing hands regularly with soap and water protects man from getting infected with the parasites [20], although other studies reported otherwise [1], [21]. Some records have documented that children engaged with washing habit had lower levels of medical leave from school [22], [23]. In Indonesia, since a lot of people eat with bare hands particularly in rural community, hand-washing is mostly practiced prior to eat than after defecation.…”
Section: B Intestinal Protozoa Infections and Risk Factorsmentioning
confidence: 99%